1987
DOI: 10.1111/j.1751-1097.1987.tb04800.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Pigmented Human Cells to Killing by Sunlight and Oxygen Radicals

Abstract: Solar irradiation of a panel of human cell lines revealed three phenomena relevant to understanding the biological role of melanin; a heavily melanised melanoma line (MM418) was considerably more resistant to solar killing compared with HeLa and amelanotic melanoma cells of similar size and DNA content; MM418 cells were also resistant to killing by artificial UVB and by hydrogen peroxide generated in situ with extracellular glucose oxidase; and no difference in survival between the cell lines was found using 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In agreement with other studies, our data revealed that UVR (in the range capable of causing sunburn in vivo) generally induces cell death and a drastic increase in the apoptotic activity in the irradiated WM cell lines, [25][26][27][28] suggesting excessive underlying DNA damage beyond the capacity of the repair system. 29 This DNA damage may be either in the form of accumulated pyrimidine dimers (induced by UVB) or oxidatively modified bases (induced by UVA).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies, our data revealed that UVR (in the range capable of causing sunburn in vivo) generally induces cell death and a drastic increase in the apoptotic activity in the irradiated WM cell lines, [25][26][27][28] suggesting excessive underlying DNA damage beyond the capacity of the repair system. 29 This DNA damage may be either in the form of accumulated pyrimidine dimers (induced by UVB) or oxidatively modified bases (induced by UVA).…”
Section: Discussionsupporting
confidence: 92%
“…2). Exposure of cultured human melanoma cells to UVB has resulted in greater resistance of a heavily melanized line as compared with an amelanotic line (9). The first report of a direct effect of UVB on melanocytes, rather than melanoma cells, was based on cultured human cells (10).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, highly melanotic melanocytes, but not melanocytes with a low melanin content, exhibited an increase in melanin content following UV exposure (60). Another study comparing melanoma cells with different melanin contents also found that melanotic melanoma cells were more resistant to the cytotoxic effect of UVB than amelanotic melanoma cells (61). Further comparison of the responses of melanoma cells with different melanin contents to UVB showed that the most melanotic cells had the least amount of photoproducts and were most resistant to cytotoxicity (62).…”
Section: Constitutive Melanin Content and The Response Of Cultured Humentioning
confidence: 98%